2018
DOI: 10.1128/iai.00237-18
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Staphylococcus epidermidis in Fibroblasts and Osteoblasts

Abstract: is a leading cause of infections associated with indwelling medical devices, including prosthetic joint infection. While biofilm formation is assumed to be the main mechanism underlying the chronic infections causes, we hypothesized that also evades immune killing, contributing to its pathogenesis. Here, we show that prosthetic joint-associated isolates can persist intracellularly within human fibroblasts and inside human and mouse osteoblasts. We also show that the intracellularly persisting bacteria reside p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 86 publications
(110 reference statements)
0
17
0
Order By: Relevance
“…Since then, SCVs were found in a wide range of bacterial species such as S. aureus [181] and CoNS species and are generally correlated to biomaterial-associated infections [180,182]. Several aspects of the pathogenic potential of SCVs have been described, mainly their enhanced biofilm-forming ability [183], evasion from the immune system response [184], and their resistance against antimicrobial agents [185,186]. Interestingly, Onyango et al revealed that S. epidermidis and S. lugdunensis were capable of developing SCVs pheno-types following the exposure to a wide range of environmental stress conditions, such as pH alterations (pH5), osmotic stress (0-20% NaCl), low temperature (4 • C), and to the presence of antimicrobial agents (vancomycin and penicillin G) [187].…”
Section: Bacterial Cells Dormant Phenotypes: a Tolerance Mechanismmentioning
confidence: 99%
“…Since then, SCVs were found in a wide range of bacterial species such as S. aureus [181] and CoNS species and are generally correlated to biomaterial-associated infections [180,182]. Several aspects of the pathogenic potential of SCVs have been described, mainly their enhanced biofilm-forming ability [183], evasion from the immune system response [184], and their resistance against antimicrobial agents [185,186]. Interestingly, Onyango et al revealed that S. epidermidis and S. lugdunensis were capable of developing SCVs pheno-types following the exposure to a wide range of environmental stress conditions, such as pH alterations (pH5), osmotic stress (0-20% NaCl), low temperature (4 • C), and to the presence of antimicrobial agents (vancomycin and penicillin G) [187].…”
Section: Bacterial Cells Dormant Phenotypes: a Tolerance Mechanismmentioning
confidence: 99%
“…Internalization of S. epidermidis in osteoblasts is more controversial. In in vitro models, two papers reported an almost total lack of internalization (Valour et al, 2013; Campoccia et al, 2016), whereas a recent paper by Perez and Patel reported the ability of two clinical strains of S. epidermidis to penetrate osteoblasts (Perez and Patel, 2018). However, the level of internalization is similar in the three papers (around 100 intracellular staphylococci per 100,000 osteoblasts).…”
Section: Staphylococcal Biofilmmentioning
confidence: 99%
“…In another study, mice vaccinated with a recombinant form of the adhesin showed significant reduction in the sepsis-associated mortality rate (13% vs 87% in non-vaccinated group) [ 56 ]. Similarly, guniea pigs infected with mutant S. aureus strain i.e defective in expression of fibronectin-binding protein showed three times less adherence to miniplates implanted in than normal wild type strains [ 57 ] stressing on the critical role that fibronectin-binding proteins (FbpA and FbpB) play in pathological course of SA. Once adhered, the bacteria multiply using the synovial milieu as an ideal culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…Once adhered, the bacteria multiply using the synovial milieu as an ideal culture medium. Recent evidence have suggested the existence of biofilm-like clumps or agglomerates for S. aureus and MRSA strains in the synovial fluid of patient suffering from chronic joint infections and septic arthritis [ 57 59 ]. Pestrak et al [ 60 ] highlighted on the role of host factors such as fibrinogen and fibronectin in the formation of such biofilm-like aggregates within the joint fluid.…”
Section: Methodsmentioning
confidence: 99%